Ultrafast Laser Shock Straining in Chiral Chain 2D Materials: Mold Topology-Controlled Anisotropic Deformation - Liu, Xingtao; Branco, Danilo de Camargo; An, Licong; Wang, Mingyi; Jiang, Haoqing; Wang, Ruoxing; Wu, Wenzhuo; Cheng, Gary J. (Nano-Micro Letters, 2025)
Tellurene, a chiral chain semiconductor with a narrow bandgap and exceptional strain sensitivity, emerges as a pivotal material for tailoring electronic and optoelectronic properties via strain engineering. This study elucidates the fundamental mechanisms of ultrafast laser shock imprinting (LSI) in two-dimensional tellurium (Te), establishing a direct relationship between strain field orientation, mold topology, and anisotropic structural evolution. This is the first demonstration of ultrafast LSI on chiral chain Te unveiling orientation-sensitive dislocation networks. By applying controlled strain fields parallel or transverse to Te’s helical chains, we uncover two distinct deformation regimes. Strain aligned parallel to the chain’s direction induces gliding and rotation governed by weak interchain interactions, preserving covalent intrachain bonds and vibrational modes. In contrast, transverse strain drives shear-mediated multimodal deformations—tensile stretching, compression, and bending—resulting in significant lattice distortions and electronic property modulation. We discovered the critical role of mold topology on deformation: sharp-edged gratings generate localized shear forces surpassing those from homogeneous strain fields via smooth CD molds, triggering dislocation tangle formation, lattice reorientation, and inhomogeneous plastic deformation. Asymmetrical strain configurations enable localized structural transformations while retaining single-crystal integrity in adjacent regions—a balance essential for functional device integration. These insights position LSI as a precision tool for nanoscale strain engineering, capable of sculpting 2D material morphologies without compromising crystallinity. By bridging ultrafast mechanics with chiral chain material science, this work advances the design of strain-tunable devices for next-generation electronics and optoelectronics, while establishing a universal framework for manipulating anisotropic 2D systems under extreme strain rates. This work discovered crystallographic orientation-dependent deformation mechanisms in 2D Te, linking parallel strain to chain gliding and transverse strain to shear-driven multimodal distortion. It demonstrates mold geometry as a critical lever for strain localization and dislocation dynamics, with sharp-edged gratings enabling unprecedented control over lattice reorientation. Crucially, the identification of strain field conditions that reconcile severe plastic deformation with single-crystal retention offers a pathway to functional nanostructure fabrication, redefining LSI’s potential in ultrafast strain engineering of chiral chain materials. Highlights: 1 Realized ultrafast laser shock imprinting on chiral chain tellurene: Reveals crystallographic orientation-dependent deformation in 2D tellurium via laser shock imprinting. 2 Dual deformation regimes: Identifies two distinct strain response modes—parallel strain enables chain gliding and rotation, while transverse strain induces multimodal shear-driven deformations, dramatically altering lattice structure and properties. 3 Mold topology enabled strain localization and single-crystal retention—sharp edges generate localized shear, forming dislocations more effectively than smooth molds. Asymmetric strain achieves dense deformation while preserving single-crystal zones, enabling precise optoelectronic nanostructuring.